Stagnation or Revival? Palestinian Economic Prospects - World Bank (Washington, DC, 2012)
The Palestinian Authority (PA) continues to experience a severe fiscal crisis, which threatens to become protracted given recent and projected declines in donor assistance. The PA is making a concerted effort to strengthen its fiscal position, including taking steps to raise domestic revenues and control expenditures. However, these efforts will not be successful unless they are supported by concrete and known actions of the Government of Israel, such as the sharing of relevant tax information on Palestinian revenues. In addition, in the short-term it is imperative that additional donor funding be identified as the PA simply cannot take enough steps to reduce the projected recurrent deficit to the currently expected level of aid. A continuation of the current trend of reduction in donor aid would likely aggravate the Palestinian fiscal crisis, potentially jeopardizing gains made in recent years in institution-building.